An accurate and practical method for assessing science and engineering problem-solving expertise. Issue 13 (2nd September 2022) - Price, Argenta; Salehi, Shima; Burkholder, Eric; Kim, Candice; Isava, Virginia; Flynn, Michael; Wieman, Carl
ABSTRACT: The ability to solve authentic real-world problems in science, engineering, and medicine is an important goal in post-secondary education. Despite extensive research on problem solving and expertise, the teaching and assessing of advanced problem-solving skills in post-secondary students remains a challenge. We present a template for creating assessments of advanced problem-solving skills that is applicable across science, engineering, and medical disciplines. It is based on a cognitive model of the problem-solving process that is empirically grounded in the study of skilled practitioners ('experts') solving authentic problems in their disciplines. These assessments have three key features that overcome shortcomings of current assessment approaches: 1) a more authentic amount and sequence of information provided, 2) opportunities for students to make decisions, and 3) scoring based on comparison with skilled practitioners. This provides a more complete and accurate assessment of authentic problem-solving skills than currently exists for science, engineering, and medicine. Such assessments will be valuable to instructors and curriculum designers for evaluating and improving the teaching of problem solving in these disciplines. We provide examples of problem-solving assessments that illustrate the use of this template in several disciplines.